Phenotypic and genotypic characteristics of enterobacteriaceae from Rayu river, sarawak - Yong, Sy Fuh (Universiti Malaysia Sarawak, UNIMAS, 2012)
Enterobacteriaceae are normal inhabitants of gastrointestinal tract of warm blooded animals and human which some of them are associated with pathologic processes in gastrointestinal tract. Waterborne and foodborne diseases has been increasing over years which raise the global concern whereby river serves as a potential transmission pathway for enterobacteriaceae to threaten human health. In this study, the enterobacteriaceae were successfully isolated by using EMB agar from samples collected from Rayu River. Gram-lysis test was carried out to differentiate gram-positive and gram-negative bacteria. The isolates were further identified by using API 20E kit and it was found that most of the isolates were Serratia (29.11%) and the least was Escherichia (1.27%). The antimicrobial susceptibility test shows that all of the isolates were susceptible to sulphamethoxazole trimethoprim (100%) while high resistant to nitrofurantoin and carbenicillin. High MAR index value obtained is ranged from 0.50 to 0.75. These values indicate that these isolates were originated from high risk sources where antibiotics are commonly used. LAMP result showed that none of the E. coli isolates from Rayu River consists of the virulence gene to produce Shiga toxin. Meanwhile, (GTG)5-PCR fingerprinting analysis revealed that the genomes of enterobacteriaceae isolates were highly diverse and well distributed as indicated by 6 major and minor clusters in the dendrogram.